Congenital anomalies during the 2015-2018 Zika virus epidemic: a population-based cross-sectional study - Fabio Antonio Venancio; Maria Eulina Quilião; Danielli de Almeida Moura; Micael Viana de Azevedo; Sahra de Almeida Metzker; Lisany Krug Mareto; Márcio José de Medeiros; Cláudia Du Bocage Santos-Pinto; Everton Falcão de Oliveira (BMC, 2022)
Abstract Background Congenital anomalies are associated with several clinical and epidemiological complications. Following the Zika epidemic onset in Latin America, the incidence of congenital anomalies increased in Brazil. This study aimed to determine the frequency of congenital anomalies in one Brazilian state and assess potential factors associated with them. Methods This cross-sectional descriptive study was based on data concerning congenital anomalies recorded in the Brazilian Live-Born Information System during the Zika epidemic in Mato Grosso do Sul state from 2015 to 2018. Congenital anomalies were stratified according to year of birth and classified using ICD-10 categories. Results In total, 1,473 (0.85%) anomalies were registered. Within the number of cases recorded, microcephaly showed the greatest frequency and variations, with a 420% increase observed in the number of cases from 2015 to 2016. We identified an increase in the incidence of central nervous system anomalies, with the highest peak observed in 2016 followed by a subsequent decrease. Musculoskeletal, nervous, and cardiovascular system anomalies, and eye, ear, face, and neck anomalies represented 73.9% of all recorded anomalies. There was an increased chance of congenital anomalies in uneducated (odds ratio [OR] 5.56, 95% confidence interval [CI] 2.61-11.84) and Indigenous (OR 1.32, 95% CI 1.03-1.69) women, as well as among premature births (OR 2.74, 95% CI 2.39-3.13). Conclusions We estimated the incidence of congenital anomalies during the Zika epidemic. Our findings could help to support future research and intervention strategies in health facilities to better identify and assist children born with congenital anomalies.